Prevalence of menopause, chronic illnesses and life style of middle aged women in Karachi, Pakistan - Sarah Saleem; Uzma Shamsi; Syed Iqbal Azam; Fatima Jalil; Sameera Ali Rizvi (Al Ameen Medical College, 2012)
: Objectives: To determine the prevalence of menopause, chronic illnesses and lifestyle of middle aged women in Karachi, Pakistan. Design: A Cross Sectional survey was conducted among women of 40-60 years living in socio-economically different areas of Karachi. Information was gathered on their current menstrual status, age at menopause, body mass index, exercise habits, weekly recall of food consumed and chronic illnesses. These variables were also examined according to the socio economic status of the area where women reside. Results: A total of 1764 women in age group 40-60 years were interviewed. The prevalence of menopausal women in this age group was 39.3 percent (%). The mean age at menopause was 45.2 (±3.8) years. Only seven percent of women were doing some kind of exercise and approximately eighty percent had their Body Mass Index ≥ 23 kg/m2 according to Asian Standard. Approximately 31 percent (%) of women reported eating any type of meat at least four times a week, of these most were from higher income area. Majority consumed meat less than three times a week. Similar pattern was observed for consumption of fruits and milk. Approximately 36 percent (%) of women reported diabetes mellitus, hypertension, cardio vascular heart disease and arthritis. Conclusion: The sedentary life style, obesity and chronic illnesses are highly prevalent and are serious emerging public health problem for 40-60 years old women of Karachi. We recommend that awareness about balanced diet, exercise and healthy eating habits should be inculcated in women early in life, where possible through schools and media. Health policies and public health messages should be formulated according to the various stages of life cycle of women, so that women can prepare themselves for the next stage of life.